Contributing to Financial Crisis Prevention Through Banking and Financial Services Regulation - Krambia-Kapardis, Maria (My University, 2016)
Anabtawi and Schwarcz (2013)2 remind us that financial firms and financial markets operate in the con-text of various regulatory bodies that, generally speak-ing, “govern the provision, allocation, and deployment of financial capital.”3 At the same time, relevant legisla-tion provides for penalties to (a) prevent breaches of the regulatory framework, (b) mitigate the adverse conse-quences of breaches of the regulatory framework, and (c) reduce the likelihood of further losses.4 Markets, of course, exist in order to exchange assets and the formulations of explicit rules that govern or control this process are vitally important for efficiently pricing traded assets.
Keywords: Financial Modernization Act; financial firm; financial markets; financial capital; Government financial regulations